(untitled) (Journal of Informatics and Mathematical Sciences, 2013)
In this paper, the authors discuss the asymptotic behavior of solutions of the generalized nonlinear α-difference equation equation Δ_α()(p(k)Δ_α() u(k))+f(k)F(u(k))=g(k), equation k[a,∞), where the functions p, f, F and g are defined in their domain of definition and α>1, is positive real. Further, uF(u)>0 for u eq0, p(k)>0 for all k[a,∞) for some a[0,∞) and for all 0≤ j<, R_a+j,k→∞, where R_t+j,k=_r=0^k–t-j1p(t+j+r), t[a,∞) and kN_(t+j+).